APPLICATION OF VIRTUAL REALITY (VR) ON PAIN SCALE IN POST-OPERATIVE FRACTURE PATIENTS: A CASE STUDY - Handayani, Yunita Mukti; Prastiwi, Firman (Journal of Advanced Nursing and Health Sciences, 2026)
Background: A fracture is a bone break that is usually caused by trauma or physical force. The force of impact, the condition of the bone, and the soft tissues around it will determine the severity of the fracture. The problem in fracture patients usually arises in postoperative patients, which is pain. The objective of this case study is to understand the nursing care provided to post-operative fracture patients experiencing acute pain through a virtual reality (VR) intervention.Methods: This research is descriptive, using a case study approach of a single patient post-fracture surgery in the Sakura room at Dr. Soeratno Gemolong Regional General Hospital. Case data collection was conducted for 3 consecutive days, from February 12th to 14th, 2025, with a single 15-minute virtual reality (VR) session featuring a video of natural scenery.Results: The study shows that virtual reality (VR) reduces pain scores in post-fracture patients, from 6 (moderate pain) to 3 (mild pain).Conclusion: This virtual reality (VR) intervention is effective in reducing pain levels in post-operative patients.